[PP.37.18] DIFFERENT CORRELATES OF LEFT AND RIGHT CAROTID ARTERIAL STIFFNESS IN HYPERTENSIVE PATIENTS. (September 2016) - Bilo, G.; Lonati, L.M.; Lan, G.; Giuli, V.; Guida, V.; Parati, G.
Abstract : Objective: Local arterial stiffness (AS) of common carotid arteries (CCA) can be noninvasively investigated by ultrasonography and was reported to independently predict incident stroke. Several studies reported on asymmetry between right (R) and left (L) CCA in terms of intima-media thickness but little is known on AS symmetry and determinants of right and left carotid AS. Aim of our study was to investigate this issue in middle-aged essential hypertensive patients. Design and method: Thirty outpatients (age 51.7 ± 6.7 [39–63] years, M/F 13/17, BMI 26.9 ± 5.6 kg/m2, 20 on antihypertensive treatment) underwent carotid ultrasonography with AS measurement in radiofrequency (QAS, MyLab Class C, Esaote, Italy). Associations of AS with conventional and 24 h blood pressure, as well as with other vascular indices (CCA intima-media thickness in radiofrequency [IMT], carotid-femoral pulse wave velocity [cfPWV, PulsePen, DiaTecne, Italy], cardio-ankle vascular index [CAVI; VaSera, Fukuda Denshi, Japan]) were assessed. Results: There was no significant difference in mean carotid pulse wave velocity (carPWV) between R and L CCA (7.5 ± 1.5 vs 7.7 ± 1.6, p = 0.6), while IMT was slightly smaller in R than in L CCA (0.61 ± 0.11 vs 0.65 ± 0.09 mm, p < 0.005). Table shows coefficients of univariate correlation (r) between carPWV in L and R CCA and the assessed variables. In multiple regression models which included age, sex, BMI, 24 h SBP, 24 h DBP, CAVI and cfPWV, carPWV in R CCA was independently associated only with CAVI (beta = 0.38, p = 0.03) while carPWV in L CCA only with 24 h DBP (beta = 0.60, p = 0.05). Figure. No caption available. Conclusions: Our data suggest that in middle-aged hypertensive subjects local stiffness of R and L carotid artery may have different determinants, possibly due to anatomical differences: R is more closely associated with indices of global vascular aging while L, directly emerging from aortic arch, seems to depend mostly on blood pressure level. These findings, if confirmed in larger studies, may be relevant for identification of possible determinants of cerebrovascular complications in hypertensive patients.